The Multiple Socialization Of Organization Members - Feldman, Daniel C. (Academy of Management Review, 1981)
An integrated model is presented of three relatively distinct views of organizational socialization: the development of work skills and abilities; the acquisition of a set of appropriate role behaviors; and the adjustment to the work group's norms and values. A theoretical rationale is developed to explain the contingencies on which progress through the different socialization processes depend. Three attitudinal variables (general satisfaction, internal work motivation, job development) and three behavioral variables (carrying out role assignments dependably, remaining with the organization, innovation/spontaneous cooperation) are suggested as criteria for measuring progress in socialization.